Preliminary estimation of the tolerance limit of Coffea arabica to the lesion of Pratylenchus coffeae in green-house condition - Phap, Trinh Quang; Chau, Nguyen Ngoc (Academia Journal of Biology, 2014)
Based on the Seinhorst model y = ym for Pi £ T, and y = ym.m + ym (1-m)z(Pi-T), the tolerance limit, viz. economic threshold of Coffea arabica cv. catimor to the lesion of Pratylenchus coffeae was preliminary identified in the green-house conditions. The tolerance limit of C. arabica cv. catimor to the lesion of P. coffeae in 30, 60 and 90 days after incubation were estimated a range from 0-1.66 nematodes/cm3 soils. The correlation value with R2 from 0,64 to 0,94 was shown the close relation between initial population densities of P. coffeae with the coffee yielded possibilities. This was also shown the seedlings of C. arabica cv. catimor were susceptible with P. coffeae. The reproduction capacity of P. coffeae after 30 and 60 days inoculated with densities between 250 and 8000 nematodes/pot were resulted below 1 that were also meaning negative growth of those populations. It’s only positive population growth with inoculated density of 250 nematode/pot and 90 days after inoculation. This result has shown that the size of the initial population was closely related with the root weight of seedlings. For recovery and development of the nematode populations, it needed to be in small size of incubation density (as about 250/pot) and reasonable duration (as 90 days after inoculation) in this experiment.